Martin Heidegger dalam Seni Membuat Caption Social Media Marketing - Simonigar, Jhimshy; Kennedy Sitorus, Fitzerald (CV. ITTC INDONESIA, 2023)
This article delves into the philosophical concepts of Martin Heidegger, particularly Dasein, and its implications on understanding and interpreting language, truth, and identity in the context of creating captions on the Instagram social media platform. Through in-depth literature review, textual analysis, and a perspective analysis approach, the research demonstrates that Dasein, in the realm of social media, is involved in facticity (thrownness), understanding, and falling prey. In digital marketing, the concept of Dasein provides a foundation for understanding the audience, designing campaigns that reflect online existence, and constructing authentic digital identities. Captions serve not only as descriptions but also encapsulate subjective experiences of visual content, building atmosphere, and supporting social media marketing. By adopting Heidegger's concepts, this research provides profound insights into how language serves as an essential mirror of human identity in the context of social media, particularly Instagram.